PENGARUH CURING AIR LAUT TERHADAP KUAT TEKAN BETON DENGAN AGREGAT HALUS ABU BATU - Tisnawati, Tisnawati; Kumalasari, Dwi; Rabbani, Nauval; Abdul Malik Annasir, Muhammad; Firman, Annas; Trilaksono, Fizal (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2024)
Abstract Based on the source, aggregates can be divided into two, namely natural and artificial. Along with the increasing development of infrastructure using concrete structures, the demand for fine aggregate in the form of sand has also increased, so innovations have emerged to use artificial fine aggregate in the form of stone ash. Stone ash is a material that comes from the process of breaking down and filtering natural rock produced from crushed stone industry waste with a size of less than 0.5 cm. Stone ash was chosen as a building block for concrete because Pekalongan City frequently experiences tidal floods, resulting in the flooding of old and newly built buildings, such as roads and houses made of concrete. Concrete structures generally harden quickly and dry easily, therefore concrete curing is carried out so that the water content of the concrete does not decrease quickly, thereby producing good quality concrete. The concrete curing process is an important method for maintaining concrete quality because it not only maintains the moisture content on the inside or surface of the concrete, but also ensures that the concrete produced is of the desired quality. This research was carried out using experimental methods and was carried out at the Construction Engineering Laboratory, Pekalongan University. The objects of this research include testing materials with fine aggregate in the form of stone ash and making concrete samples to determine the effect of seawater curing on the compressive strength of concrete. The compressive strength results for well water treatment were 18,064 MPa for 14 day old concrete and 22,867 MPa for 28 day old concrete. Meanwhile, concrete treatment with sea water has a compressive strength of 16,400 MPa for 14 day old concrete and 20,416 MPa for 28 day old concrete. From these results it can be concluded that treating concrete with sea water can affect the compressive strength value of concrete. Keywords: Compressive Strength, Rock Ash, Sea Water